Virtual screening, molecular dynamics simulations, and in vitro analysis of Sophora flavescens-derived aloperine against Haemonchus contortus - Li, Anben; Ma, Yan; Li, Wenxi; Zhai, Bintao; Fu, Nana; Li, Jun; Zhou, Qianyu; Liu, Yang (Frontiers in Veterinary Science, 2025)
IntroductionThe resistance of Haemonchus contortus to ivermectin (IVM) poses a significant economic threat to the global livestock industry. This necessitates alternative strategies for managing the development of drug resistance in H. contortus.MethodsThis study employed molecular docking screening, molecular dynamics simulations, and in vitro experiments to evaluate the effects of bioactive alkaloids from Sophora alopecuroides L. on H. contortus.ResultsMolecular docking and dynamics simulations revealed aloperine (ALO)’s strong binding affinity (−6.83 kcal/mol) and stable interaction with HC-Pgp among 13 tested alkaloids. Further evaluation through larval development test (LDT), larval migration inhibition test (LMIT), and scanning electron microscopy revealed that the combined administration of ALO and IVM exerted significantly enhanced inhibitory effects on the development, motility, and morphological integrity of IVM-resistant strains compared to monotherapy groups. Furthermore, the Rhodamine-123 accumulation assay demonstrated that aloperine significantly inhibited HC-Pgp activity (p < 0.05).DiscussionThis study provides new perspectives for exploring the natural product ALO as an anthelmintic, HC-Pgp inhibitor, and synergist molecule. Further studies evaluating in vivo safety and pharmacokinetic interactions are required to validate these findings.